2020
DOI: 10.1093/femsec/fiaa181
|View full text |Cite
|
Sign up to set email alerts
|

Long-term nitrogen addition in maize monocultures reduces in vitro inhibition of actinomycete standards by soil-borne actinomycetes

Abstract: Management of soil microbial communities for enhanced crop disease suppression is an attractive approach to biocontrol, but the effects of agricultural practices on the disease-suppressive potential of the soil microbial community remain unknown. We investigated the effects of long-term nitrogen addition (103 kg ha−1 nitrogen as urea versus no fertilizer) and crop residue incorporation versus removal on in vitro antibiotic inhibitory capacities of actinomycetes from 57-year maize (Zea mays L.) monocultures in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In pathogen‐poor soils, the abundance and richness of pathogens might be less affected by competition among pathogens and biotic interactions with other microbes when faced with adverse conditions such as warming and nutrients (Delgado‐Baquerizo et al, 2020; Lekberg et al, 2021). By contrast, the more complex biotic interactions in pathogen‐rich soils could cause the abundance and richness of pathogens to gradually reach an upper asymptote limit in suitable environments, with competition leading to declines (Gieske & Kinkel, 2020; Wardle, 2006). More significant relationships found in the subsoil suggested that subsoil pathogens were more affected by the abrupt environment change, which might be associated with their indirect contact with the external environment.…”
Section: Discussionmentioning
confidence: 99%
“…In pathogen‐poor soils, the abundance and richness of pathogens might be less affected by competition among pathogens and biotic interactions with other microbes when faced with adverse conditions such as warming and nutrients (Delgado‐Baquerizo et al, 2020; Lekberg et al, 2021). By contrast, the more complex biotic interactions in pathogen‐rich soils could cause the abundance and richness of pathogens to gradually reach an upper asymptote limit in suitable environments, with competition leading to declines (Gieske & Kinkel, 2020; Wardle, 2006). More significant relationships found in the subsoil suggested that subsoil pathogens were more affected by the abrupt environment change, which might be associated with their indirect contact with the external environment.…”
Section: Discussionmentioning
confidence: 99%
“…Elsayed, Grosch and Smalla (2021) demonstrated using cultivation-dependent techniques that the potato plant sphere, and to a lesser extent the soil type, affected the diversity and proportion of bacteria showing in vitro antagonistic activity towards the soil-borne pathogen Ralstonia solanacearum. Another study described that long-term nitrogen fertilization in soils under maize monoculture resulted in fewer actinomycetes with in vitro inhibitory capacities towards other actinomycetes compared to non-fertilized soils while crop residue incorporation showed no effect (Gieske and Kinkel 2020).…”
mentioning
confidence: 99%